2020
DOI: 10.15517/rbt.v68i4.42094
|View full text |Cite
|
Sign up to set email alerts
|

Berberina, curcumina y quercetina como potenciales agentes con capacidad antiparasitaria

Abstract: Introducción: El uso indiscriminado de agentes antiparasitarios ha resultado en el establecimiento de resistencia a ellos. Por lo cual es necesario el desarrollo de nuevas alternativas de tratamiento. Los productos naturales poseen diversas cualidades como posibles coadyuvantes en terapias contra distintos agentes etiológicos, entre los que destaca sus efectos antiparasitarios. Objetivo: Evaluar la actividad antiparasitaria, antioxidante, citotóxica y citoprotectora de Berberina (Ber), Curcumina (Cur) y Querce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…The in vitro hemoglobin denaturation and hemolysis test is recommended and used for a battery of tests aimed at checking the toxicity of different products in the pharmaceutical industry, which are useful to examine therapies throughout the early stages of clinical development [ 78 ]. The hemolytic activity of plant extracts was evaluated by the hemolysis test [ 79 ]. Ten milliliters of human blood from healthy donors was collected by venipuncture in tubes with anticoagulant (EDTA), after which blood was centrifuged to separate erythrocytes from plasma at 1500 rpm (15 min at 25 °C) and washed three times with 10 mL of PBS (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro hemoglobin denaturation and hemolysis test is recommended and used for a battery of tests aimed at checking the toxicity of different products in the pharmaceutical industry, which are useful to examine therapies throughout the early stages of clinical development [ 78 ]. The hemolytic activity of plant extracts was evaluated by the hemolysis test [ 79 ]. Ten milliliters of human blood from healthy donors was collected by venipuncture in tubes with anticoagulant (EDTA), after which blood was centrifuged to separate erythrocytes from plasma at 1500 rpm (15 min at 25 °C) and washed three times with 10 mL of PBS (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it has been proven to have toxic effects, has been considered a potential carcinogen, and has presented cytotoxicity, mutagenicity, and embryotoxic and teratogenic effects [7]. Therefore, it is necessary to find new alternatives such as natural products like plants [8]. Plants are a source of bioactive molecules because they have properties reported as antimicrobial, antiparasitic, anticancer, healing, analgesic, anti-inflammatory, and tissue repairing, among others, and represent a potential alternative in pulp treatment [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies in human cell lines have demonstrated the cytotoxic capacity of several natural extracts [55,56] such as curcuminoids [16]. Different components of Zingiberaceae plants can suppress the activity of some common mutagens and carcinogens in various cell types in both in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%